Comparative efficacy and safety of anti-HGF/MET pathway agents plus chemotherapy versus chemotherapy alone as first-line treatment in advanced gastric cancer: a protocol for a systematic review and meta-analysis. Issue 12 (24th December 2021) - Jiang, Zhiyuan; Cai, Zhaolun; Ma, Qin; Shen, Chaoyong; Yin, Yuan; Yin, Xiaonan; Liu, Chunyu; Chang, Chen; Zhao, Zhou; Mu, Mingchun; Zhang, Bo
Abstract : Introduction: Phase I/II clinical trials suggested that the hepatocyte growth factor (HGF)/mesenchymal-epithelial transition (MET) pathway-targeted agents were active in suppression of gastric cancer (GC). Randomised controlled trials (RCTs) were undertaken assessing whether the addition of anti-HGF/MET agent (rilotumumab or onartuzumab) to chemotherapy improves survival outcomes of advanced GC, but conflict conclusions were reached. Therefore, we plan to perform this systematic review and meta-analysis to synthesise evidence concerning efficacy and safety of anti-HGF/MET agents combined with chemotherapy as the first-line treatment to advanced GC. Methods and analysis: Systematic searches of the PubMed, Embase and the Cochrane Central Register of Controlled Trials will be performed with no language restriction from inception to 31 January 2022 to identify RCTs exploring the comparative efficacy and safety of anti-HGF/MET agents plus chemotherapy as first-line treatment in advanced GC. The primary outcome will be the time-to-event progression-free survival and overall survival, and the secondary outcomes will be disease control rate, overall adverse events rate and grade 3–5 adverse events rate. Statistical heterogeneity will be assessed by visual inspection of forest plots and measured using the I 2 statistics. A fixed-effect model will be used when heterogeneity is low otherwise, a random-effect model will be chosen. Publication bias will be assessed by funnel plots; subgroup analysis and sensitivity analysis will be performed in the right context. For each outcome, we will perform data synthesis using Rev Man V.5.3 software, and compile 'summary of findings' tables using GRADEpro software. Ethics and dissemination: There is no requirement for ethics approval because no individual data will be collected in this research. It is anticipated that the dissemination of results will take place at conferences and through publication in a peer-review journal, any adjustments from the protocol will be clearly documented and explained in its final report. PROSPERO registration number: CRD42020177404.